NON PERFORMING LOAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI - Putra Abyanta (Fakultas Ekonomi, Program Studi Akuntansi, Universitas Warmadewa, 2020)
A bank that extends credit will carry a risk that is, in the form of non-performing credit payments or commonly referred to as credit risk. Credit risks such as non-performing loans or often referred to as Non-Performing Loans. NPL is an indication of a problem in the bank which if not immediately get a solution it will have a negative impact on the bank. This study aims to determine the effect of Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and Company Size on Non-Performing Loans (NPL) on General Banking Companies listed on the Indonesia Stock Exchange Period 2016-2018. The study population was 45 general banking companies listed on the Indonesia Stock Exchange for the period of 2016-2018. The data analysis method used is multiple linear regression with a significance level of 0.05. The results showed that LDR affected NPL, while CAR and Company Size did not significantly influence NPL.